Effect of an Acid Antimicrobial on Turkey Breast Meat Salmonella and Total Aerobes - Smith , D.P. (International Journal of Poultry Science, 2012)
Acid solutions have been used as antimicrobials on meat and poultry. FreshFx is a commercially-available surface treatment for the reduction of pathogens and extension of shelf life of raw poultry. Two replicate trials were conducted to determine the effect of FreshFx on numbers of total aerobes and inoculated Salmonella on raw turkey breast meat during 14 d of refrigerated storage. In each trial, three turkey breast meat cutlets, obtained at retail, were inoculated with nalidixic acid-resistant Salmonella and cut in half. One half was dipped in FreshFx for 30 s and the other half dipped in water for 30 s as a control, then all cutlet halves were refrigerated at 4°C and sampled at 0, 1, 2, 7, 10 and 14 d for total aerobic bacteria and Salmonella. No reduction (P>0.05) in numbers of total aerobes or Salmonella was observed due to FreshFx. Mean log cfu for total aerobes was 7.1 on d 0 and 7.8 on d 14. Mean pooled Salmonella log cfu were 6.9 on d 0 and 5.1 on d 14. Total aerobe counts were artificially high on d 0 to 10 due to the large numbers of Salmonella initially inoculated onto the samples. The persistence of Salmonella on samples during refrigerated storage reinforces the concept of reducing or eliminating pathogens prior to packaging and cold storage. In this experiment FreshFx did not improve shelf life as measured by reduction of total aerobes during refrigerated storage, nor reduce numbers of inoculated Salmonella on raw turkey breast meat.